The effect of ionic and non-ionic surfactants and pH on the stability, adsorption and electrokinetic properties of the alginic acid/alumina system. (1st November 2017) - Grządka, E.; Matusiak, J.
Highlights: Alginic acid (AA) adsorbs on alumina surface and the process depends on pH. CTAB interacts with AA which causes steric stabilization of the system. SDS does not interact with AA, but causes depletion stabilization. Triton X has no influence on both stability and adsorption of AA on alumina. Abstract: The influence of ionic (CTAB; SDS) and non-ionic (TX-100; TX-165 and TX-405) surfactants as well as pH of the solution on the stability, adsorption and electrokinetic properties of the alginic acid (AA)/alumina (Al2 O3 ) suspensions was studied. The results obtained using the spectrophotometric method show that the addition of ionic surfactants is an effective way to obtain stable AA/Al2 O3 suspensions whereas the changes in pH are not sufficient. Surface tension measurements together with the adsorption data show that the macromolecules of alginic acid are able to form complexes with CTAB, however, they compete for the adsorption centers on the metal oxide surface with SDS. Non-ionic surfactants do not affect alginic acid adsorption. The electrokinetic measurements (surface charge density and zeta potential measurements) prove that adsorption of alginic acid on Al2 O3 with or without surfactants changes the structure or the compact and diffused parts of the electric double layer. It should be emphasized that the alginic acid/surfactant/alumina system has not been studied before which confines its possible applications in the fields of functionalized materials.